Variation characteristics and influencing mechanisms of CO2 flux from grassland ecosystem in the Central Tianshan Mountains, China - Kun Zhang; Yu Wang; Ali Mamtimin; Yongqiang Liu (Ecological Indicators)
The intensification of carbon dioxide (CO2) fluxes in grassland ecosystems due to global climate change makes the achievement of carbon neutrality goals more challenging, particularly in arid regions with sensitive climates and fragile ecological environments. We employed the eddy covariance (EC) system to quantify CO2 flux data and conducted a comprehensive analysis of the carbon balance in the alpine grassland ecosystem situated in the Central Tianshan Mountains. Multiple environmental factors were integrated for an attribution analysis of CO2 flux using advanced systems, including random forest model, hyperbolic tangent model, future scenario simulation, and stepwise multiple regression model. The results indicate that the Central Tianshan Mountain grassland ecosystem acts as a net carbon sink with an annual carbon sequestration capacity of 1.134 × 107 ton. When the photosynthetically active radiation (PAR) exceeds 1250 µmol m−2 s−1, the grassland ecosystem enters a state of light saturation. Under the SSP126, 245, and 585 scenarios, the grassland ecosystem carbon sink rates increase by 0.2 %, 0.7 %, and 0.9 % per degree Celsius for soil temperature and by 0.4 %, 1.17 %, and 1.28 % per degree Celsius for air temperature by the year 2100. This study provides reference data for CO2 fluxes in arid grassland ecosystems, enhances our understanding of the significance of grasslands in global carbon cycling, and offers crucial insights into the absence of carbon sinks in dry regions worldwide.